Alternative bio-acidification process to make mango vinegar (LACCEI, 2024)
The aim of this research was to evaluate the synthesis of acetic acid (bio-acidification) during the elaboration of a mango-based vinegar with a microbial multistarter of yeasts and bacteria called SCOBY (symbiotic culture of bacteria and yeast) that is used to elaborate kombucha and that has the capacity to carry out alcoholic fermentation and acetic fermentation simultaneously. This method was compared with the bio-acidification using the traditional method of making vinegar, which uses alcoholic fermentation wirh Saccharomyces cerevisiae and subsequent acetic fermentation with acetic acid bacteria. In the vinegars obtained, the acidity level established by the reference regulations of 50 g/L of total acidity was reached in periods of time between 26 and 42 days for the fermentations with SCOBY of kombucha, while the traditional process (fermentation alcoholic + acetic fermentation) allowed to reach that acidity between 39 and 48 days. In addition, no significant differences were found in the content of phenolic compounds between both bio-acidification methods when using fermenters with the same dimensions. These results indicate that the fermentative process with the SCOBY multistarter allows a similar production of acetic acid than the traditional method, but in less time.